Distribution of Legionella pneumophila in Thermal Pools. Issue 5 (1st February 2016) - Walczak, Maciej; Burkowska‐But, Aleksandra; Swiontek Brzezinska, Maria; Krawiec, Arkadiusz
Abstract : The study was aimed at assessing whether there is a risk of Legionella pneumophila in thermal pools used in balneotherapy and recreation. Water samples were collected from five thermal baths, supplied by thermal waters. The total number of bacteria was determined in the direct microscopic count under a fluorescence microscope. The numbers of bacteria from investigated phylogenetic groups ( Legionella sp. and L. pneumophila ) were estimated with the use of a fluorescence in situ hybridization method. The highest average total number of bacteria in the entire research cycle was recorded in old pools labeled OB1 and OB2. Bacteria belonging to the Legionella genus along with L. pneumophila were identified in all water samples collected from each bath. Moreover, a biofilm containing cells of L. pneumophila was identified in the collected water samples. The number of bacteria in water was dependent on the bath's age, the operation and the maintenance of the facilities. In old pools, with water exchanged periodically, the risk of L. pneumophila was higher; in new pools with a continual flow of water, lower. The results of this research showed no correlation between the number of Legionella and water temperature. Legionella pneumophila can successfully develop not only in fresh water bodies but in thermal baths as well. Still, it is uncertain whether the commonly applied culture method, developed for freshwater bodies, is also suitable for thermal baths. Abstract : The study was aimed at assessing whether there is a risk of Legionella pneumophila in thermal pools used in balneotherapy and recreation. The number of Legionella in the pools depends on the age, the operation and the maintenance of the facilities. Older pools (used for balneolotherapy) with water exchanged periodically always contained a higher number of these pathogens.